Lawyers’ question content and children’s responses in Scottish criminal courts - Andrews, Samantha J. (Psychology, crime & law, 2019)
Differences between prosecutors and defense lawyers with respect to the centrality of the information sought and topic of the questions asked, and the effects on witnesses’ responses, were examined in 56 trial transcripts of 5- to 17-year-old children testifying as alleged victims of sexual abuse. Over 40% of all questions focused on peripheral content and defense lawyers asked more questions prompting peripheral information than prosecutors. Overall, children were more productive to questions that prompted central information than questions that prompted peripheral information, and to questions seeking information about actions rather than any other topic, particularly when prompted by prosecutors. However, children were less responsive, and expressed more uncertainty and self-contradictions in response to questions that prompted central information than peripheral information. Lawyers did not alter the centrality of the information sought or topic of their questions when prompting children of different ages. These findings suggest that the centrality of the information sought and question topic are important parameters to consider when evaluating children’s responses to different types of questions.